The craft of interviewing in realist evaluation. (July 2016) - Manzano, Ana
Pawson and Tilley suggest a unique strategy for conducting qualitative interviews within realist evaluation studies. Theories are placed before the interviewee for them to comment on with a view to providing refinement. The subject matter of the interview is the researcher's theory and interviewees confirm, falsify, and refine this theory. This relationship – described as a teacher–learner cycle – is integral to realist evaluations. This article provides an overview of how interview techniques have been applied in realist evaluations in the last decade as well as suggesting two guiding principles. The first one relates to the design of realist studies and the second one explains how to ask questions like a realist, and proposes three different phases in realist interviews: theory gleaning, theory refining and theory consolidation. The article aims to contribute to a growing understanding of the practical and epistemological challenges presented by primary data collection in realist evaluation.